DESAIN APLIKASI ADMINISTRASI CURICULUM VITAE DOSEN DI LINGKUNGAN UNIVERSITAS MERDEKA MALANG - Rusdijanto, Rusdijanto (Universitas Merdeka Malang, 2015)
The purpose of this study was to create a design and prototype data processing lecturers Curriculum Vitae can be generated so that the output of information that has the characteristics, availability, easy to grasp, Relevant, Useful, Timely, Reliability, Accurate and Consistent The study used secondary data obtained from the documents in the civil service such as education history data. Then the document on the academic part of carrying out the education and teaching, while carrying out research and development and produce scientific papers, carry out community service from LPPM document. The amount of data is 336 people, both men and women with diverse groups of rank and in part to spread the eight positions in the work unit environment Malang Merdeka University. All the above data was collected with documentation technique is to copy the documents that are relevant to the design development curiculum vitae lecturer at Malang Merdeka University. From the results it can be concluded designing application design curiculum administration vitae can be used for academic services on campus and off campus faculty services so that the needs of faculty in academic, other needs related curiculum vitae can be served quickly. In the determination of policy, administrative application design can be used as a control tool to determine the development of each faculty in the respective majors on college Tridarma activities, also could provide another motivation for the professors to improve Tridarma activities and activities that are relevant outside the campus. DOI: https://doi.org/10.26905/jtmi.v1i1.613